Since JL is a perpendicular bisector of KM, it means that point H is the midpoint of segment KM. Thus, we have:
\[ KH = HM \]
You are given:
\[ KH = 6y + 3 \] \[ HM = 2y + 7 \]
Since \(KH = HM\), we can set the two expressions equal to each other:
\[ 6y + 3 = 2y + 7 \]
Now, we will solve for \(y\):
- Subtract \(2y\) from both sides:
\[ 6y - 2y + 3 = 7 \] \[ 4y + 3 = 7 \]
- Subtract 3 from both sides:
\[ 4y = 7 - 3 \] \[ 4y = 4 \]
- Divide by 4:
\[ y = 1 \]
Now, we can substitute this value of \(y\) back into the equation for \(HM\) to find the length of segment \(HM\):
\[ HM = 2y + 7 \] \[ HM = 2(1) + 7 \] \[ HM = 2 + 7 \] \[ HM = 9 \]
Thus, the length of segment \(HM\) is:
\[ \boxed{9} \]